Hydrogen sulfide ameliorates the kidney dysfunction and damage in cisplatin-induced nephrotoxicity in rat - Akram Ahangarpour; Amin Abdollahzade Fard; Mohammad Kazem Gharibnaseri; Taha Jalali; Iran Rashidi (Veterinary Research Forum, 2014)
Hydrogen Sulfide (H2S) prevents and treats a variety of disorders via its cytoprotective effects. However, the effects of H2S on rats with cisplatin (CP) nephrotoxicity are unclear. The aim was to study the effects of H2S on rats with CP nephrotoxicity. Thirty male Sprague-Dawley rats were divided into three groups: control group, nephrotoxic group received single dose of CP (6 mg kg-1) and nephrotoxic groups that received single dose 100 µmol kg-1 NaHS. On fifth day after injection, urine of each rat was collected over a 24-hr period. Animals were sacrificed 6 days after CP (or vehicle) treatment, and blood, urine, and kidneys were obtained, prepared for light microscopy evaluation, lipid peroxidation content and laboratory analysis. The results showed that plasma urea (226%), creatinine (271%), renal lipid peroxidation content (151%), Na and K fractional excretion, urine protein, volume and kidney weight in CP nephrotoxic rats were significantly higher and urine osmolarity and creatinine clearance lower than in controls. Increases of the proximal tubular cells apoptosis and mesangial matrix in CP nephrotoxicity group rats were observed. Hydrogen sulfide reversed the CP-induced changes in the experimental rats H2S prevented the progression of CP nephrotoxicity in rats possibly through its cytoprotective effects such as antioxidant properties.